Development of an Enzyme-Linked Immunosorbent Assay and Gold-Labelled Immunochromatographic Strip Assay for the Detection of Ancient Wool. (5th June 2018) - Wang, Bing; Gu, Jincui; Chen, Boyi; Xu, Chengfeng; Zheng, Hailing; Peng, Zhiqin; Zhou, Yang; Hu, Zhiwen
Abstract : The identification of ancient wool is of great importance in archaeology. Despite lots of meaningful information can be achieved by conventional detection methods, that is, light and electron microscopy, spectroscopy, and chromatography, the efficacy is likely to be limited in the detection of ancient samples with contamination or severe degradation. In this work, an immunoassay was proposed and performed for the identification of ancient wool. First, a specific antibody, which has the benefits of low cost, easy operation, and extensive applicability, was developed directly through immunizing rabbits with complete antigen (keratin). Then, an enzyme-linked immunosorbent assay (ELISA) and a colloidal gold-labelled immunochromatographic strip (ICS) were developed to qualitatively identify the corresponding protein in ancient wool samples unearthed from Kazakhstan and China. The anti-keratin antibody exhibited high sensitivity and specificity for the identification of modern and ancient wool. The limit of detection (LOD) of the ELISA method was 10 ng/mL, and no cross-reactions with other interfering antigens have been noted. It is concluded that the immunoassays are reliable methods for the identification of ancient wool.